Analisis Klaim Pending, Verifikasi dan Audit Pascaklaim Jaminan Kesehatan Nasional - Ulil Amri, Anugrah Aulia; Nurwahyuni, Atik (Jurnal Ekonomi Kesehatan Indonesia, 2024)
The implementation of Indonesia’s National Health Insurance (JKN) poses new challenges for hospitals as service providers. Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan, the program’s administrator, now routinely conducts post-claim verifications and audits after claims have been paid. This often results in claim adjustments or even full reversals of previously reimbursed amounts. This case study examines JKN claim management at a Type D General Hospital in 2022, focusing on pending claims, verification, and post-claim audits, using a systems theory framework. Key issues in pending claims include incomplete medical records (29%), insufficient supporting documents (24%), and coding errors (21%). Post-claim problems primarily stem from problematic service episodes (39%), coding errors (31%), and incomplete medical records (22%). These challenges arise from systemic issues in the hospital's JKN claim management, necessitating improvement. Recommendations emphasize internal hospital reforms, including enhanced training programs, improved communication with leaders, accurate ICD-based diagnoses and procedures, redesigned medical record formats, and the development of electronic medical records. The study also suggests appointing functional medical staff, training for Medical Committee Chairs, and advocating for budget allocation. Furthermore, the study recommends that the Health Office improve inter-agency coordination and provide constructive input to the government regarding BPJS Kesehatan’s post-claim audit practices, which often deviate from regulations. Enhancing the BPJS Kesehatan application is also necessary to establish a more effective feedback mechanism for addressing JKN claim issues.